Association between handgrip strength asymmetry and cognitive function across ethnicity in rural China: a cross-sectional study - Feng, Wenjing; Ma, Mingfeng; Gao, Hanshu; Yuan, Wei; Li, Ruixue; Guo, Hui; Gu, Cuiying; Sun, Zhaoqing; Zhang, Yao; Zheng, Liqiang (Frontiers in Aging Neuroscience, 2023)
Background Recently, the association between handgrip strength (HGS) asymmetry and cognition has been revealed, but evidences are still scarce. Particularly, the association between asymmetric HGS and cognitive performance in various cognitive domains is unclear and whether this association is stable across ethnic groups is unknown. Method The population was from a longitudinal study in rural areas of Fuxin, Liaoning, China. The Chinese version of Montreal Cognitive Assessment-Basic (MOCA-BC) was used to evaluate the cognitive function. The HGS ratio was calculated as maximal non-dominant HGS divided by maximal dominant HGS. HGS ratio <0.9 or >1.1 was classified as asymmetric dominant/non-dominant HGS, respectively. Generalized linear models were used to analyze the relationship between asymmetric HGS and cognitive function adjusted for HGS, handedness, wave, age, sex, education, ethnicity, smoking, drinking, physical labor level, BMI, hypertension, diabetes and dyslipidemia. Result A total of 2,969 participants ≥50 years were included in this study. Adjusted for HGS and other confunding variables, there was an inverted U-shaped association between HGS ratio and MoCA-BC scores (Pnon–linear = 0.004). The association between HGS ratio and MoCA-BC scores was inconsistent among ethnic groups (Pinteraction = 0.048). In Han, only asymmetric non-dominant HGS was associated with lower cognitive scores [β = −0.67, 95% confidence interval (CI): −1.26 ∼−0.08, P = 0.027]; in Mongolians, asymmetric dominant HGS(β = −0.60, 95% CI: −1.35 ∼ 0.15, P = 0.115) and asymmetric non-dominant HGS (β = −0.56, 95% CI: −1.42 ∼ 0.31, P = 0.206) were all associated with lower cognitive scores, although no statistical significance was found. Asymmetric non-dominant HGS and lower HGS, but not asymmetric dominant HGS were all independently associated with impairment of Delayed Recall (OR = 1.35, 95% CI: 1.05 ∼ 1.74; OR per 5 kg decrease = 1.10, 95% CI: 1.01 ∼ 1.21) and Fluency (OR = 1.43, 95% CI: 1.15 ∼ 1.78; OR per 5 kg decrease = 1.10, 95% CI: 1.02 ∼ 1.19). Both asymmetric dominant HGS (OR = 1.34, 95% CI: 1.07 ∼ 1.67) and lower HGS (OR per 5 kg decrease = 1.21, 95% CI: 1.10 ∼ 1.32) were associated with impairment of visuoperception. Conclusion HGS and HGS asymmetry were all independently related to lower global cognitive performance. The association between HGS asymmetry and cognitive function varies among ethnic groups.